2021
DOI: 10.1002/slct.202101010
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Use of Biomass‐Derived Activated Carbon as an Electrode Material for Electroanalysis

Abstract: Activated carbon (AC), which has attracted considerable attention as an electrode material, holds much promise for electroanalysis. The unique physical and chemical properties of AC, such as the high surface area, good thermal and electrical conductivity, good anti-causticity, high stability, and low cost make it an electrode material which can generate large profits from a commercialization perspective. Number of biomassderived ACs (BACs) with a variety of pore sizes, porosity, morphology, and crystallinity h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 109 publications
(133 reference statements)
1
9
0
Order By: Relevance
“…There have many ways for utilization of sensitive and selective determination of analytes in electrochemical analysis. The electrochemical pretreatment method one of them [44–46] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have many ways for utilization of sensitive and selective determination of analytes in electrochemical analysis. The electrochemical pretreatment method one of them [44–46] …”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical pretreatment method one of them. [44][45][46] Preliminary studies revealed that the use of untreated BDD electrode in quantitative analysis of FST has the potential to cause passivation problems, especially at its high concentrations, and also reduces the repeatability and sensitivity of measurement results.…”
Section: Chemistryselectmentioning
confidence: 99%
“…This confirms the fact that after the death of the fish, adenosine triphosphate degrades to Xa which increases with storage. [1]…”
Section: Reproducibility Of Gce/accp Interference Study and Analytica...mentioning
confidence: 99%
“…[4,5] With the increasing concern over environmental and health issues, there is a great necessary to effectively and accurately detect HQ and CC. [6] However, HQ and CC are difficult to detect or separate at the same time because they are similar isomers in structures and properties. Therefore, a fast, accurate and effective method to detect HQ and CC simultaneously is one of research hotspots.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the over intake of HQ and CC may cause headache, fatigue, kidney function damage and liver function lesion, etc [4,5] . With the increasing concern over environmental and health issues, there is a great necessary to effectively and accurately detect HQ and CC [6] . However, HQ and CC are difficult to detect or separate at the same time because they are similar isomers in structures and properties.…”
Section: Introductionmentioning
confidence: 99%